A Simple Rapid Method for Isolating Soluble Fibrin Complexes from Fibrinogen by Treatment with Thrombin and t-AMCHA - Hayashi, Shigeru; Yamada, Kaneo (Thrombosis and Haemostasis, 1979)
Using treatment with thrombin associated with trans-aminomethylcyclohexane carboxylic acid (t-AMCHA), a simple and rapid method for isolating soluble fibrin complexes (SFC) from fibrinogen in the plasma was developed. By this procedure, the recovery rates of SFC and early FDP (mainly X) increased according to the concentration of t-AMCHA, reaching a maximum at 286 mM t-AMCHA. On the other hand, the recovery rate of fibrinogen remained below 1.5% and that of late FDP was almost 100% at all concentrations of t- AMCHA. These results suggested that SFC and FDP could be isolated from fibrinogen by thrombin and t-AMCHA (286 mM) treatment. Moreover, it was possible to isolate SFC from FDP using gel filtration after treatment with thrombin and t-AMCHA. The SFC could be quantified by assay of the eluted fractions containing SFC by the staphylococcal clumping test.